Employing Ti nano-powder dielectric to enhance surface characteristics in electrical discharge machining of AISI D2 steel - Marashi, H.; Sarhan, A.A.D.; Hamdi, M. (Elsevier, 2015)
Manufacturing components with superior surface characteristics is challenging when electrical discharge machining (EDM) is employed for mass production. The aim of this research is to enhance the characteristics of AISI D2 steel surface machined with EDM through adding Ti nano-powder to dielectric under various machining parameters, including discharge duration (T-on) and peak current (I). Surface roughness profilometer, FESEM and AFM analysis were utilized to reveal the machined surface characteristics in terms of surface roughness, surface morphology and surface micro-defects. Moreover, EDX analysis was performed in order to evaluate the atomic deposition of Ti nano-powder on the surface. The concentration of Ti nano-powder in dielectric was also examined using ESEM and EDX. According to the results, the addition of Ti nano-powder to dielectric notably enhanced the surface morphology and surface roughness at all machining parameters except T-on = 340 mu s. Of these parameters, maximum enhancement was observed at T-on = 210 mu s, where the material removal rate and average surface roughness improved by similar to 69 and similar to 35% for peak current of 6 and 12 A, respectively. Elemental analysis signified negligible Ti deposition on the machined surface while the atomic concentration of Ti was increased around the crack areas. (C) 2015 Elsevier B.V. All rights reserved.